Pengimbuhan Enzim Fitase dalam Ransum Ayam Pedaging Meningkatkan Pemanfaatan Kalsium untuk Pertumbuhan Tulang dan Bobot Badan (ADDING PHYTASE ENZYMES ON BROILER RATION INCREASING CALCIUM UTILIZATION FOR BONE GROWTH AND BODY WEIGHT GAIN) - Setiawati, Datik; Sukamto, Bambang; Wahyuni, Hanny Indrat (Jurnal Veteriner, 2016)
The aim of this research was to find out the efficiency of phytase enzymes on broiler ration inenhancingdietary calcium utilization and in improving bone growth and body weight. The research used128 broiler chicks, eight days of age, with initial body weight of 104.16 ± 13.16g. All birds were assigned inCompletely Randomized Design (CRD) with 4 treatments as follows T0 (23% protein ration), T1 (21%protein ration + 1000 FTU phytase enzymes), T2 (23% protein ration + 1000 FTU phytase enzymes), T3(23% protein ration + 1% bone meal). Each treatment was replicated four times. Bone growth and bodyweight were observed when chickens were at three weeks (starter) and six weeks (finisher) of age.Theresults showed that addition of phytase enzymes in the diet had no significant effect (P>0,05) on the lengthand weight of femur, Ca retention, bone Ca mass finisher, and bone strenght, but significant (P<0,05) onCa consumption, rate of growth finisher, and Ca mass starter. Duncan test results on all parameters, T1showed the highest value. The conclusion of this research is adding phytase enzymes in the 21% proteinration have best results in bone growth starter and rate of growth finisher.
Keywords: phytase enzymes, dietary protein, broiler chickens, bone growth, bone Ca